2021
DOI: 10.3390/ijms22052490
|View full text |Cite
|
Sign up to set email alerts
|

ANT1 Activation and Inhibition Patterns Support the Fatty Acid Cycling Mechanism for Proton Transport

Abstract: Adenine nucleotide translocase (ANT) is a well-known mitochondrial exchanger of ATP against ADP. In contrast, few studies have shown that ANT also mediates proton transport across the inner mitochondrial membrane. The results of these studies are controversial and lead to different hypotheses about molecular transport mechanisms. We hypothesized that the H+-transport mediated by ANT and uncoupling proteins (UCP) has a similar regulation pattern and can be explained by the fatty acid cycling concept. The recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 69 publications
5
59
0
Order By: Relevance
“…However, unlike for UCP1, FAs were suggested to bind within the ANT translocation pathway as cofactors rather than transported species [ 12 ]. However, more recent experimental findings from using purified recombinant ANT1 reconstituted in the planar lipid bilayers reveal that ANT1 mediates H + transport only in the presence of long-chain FAs and the results support the FA cycling mechanism for H + transport [ 83 ].…”
Section: Antioxidant Synergy Of Ipla2γ and Mitochondrial Uncoupling Proteinsmentioning
confidence: 86%
“…However, unlike for UCP1, FAs were suggested to bind within the ANT translocation pathway as cofactors rather than transported species [ 12 ]. However, more recent experimental findings from using purified recombinant ANT1 reconstituted in the planar lipid bilayers reveal that ANT1 mediates H + transport only in the presence of long-chain FAs and the results support the FA cycling mechanism for H + transport [ 83 ].…”
Section: Antioxidant Synergy Of Ipla2γ and Mitochondrial Uncoupling Proteinsmentioning
confidence: 86%
“…Figure 2A shows that the specific conductance of membranes containing DNP in the presence of ANT1 (ANT1 + DNP, red column; G m = 80.9 ± 9.4 nS/cm 2 ) was approximately double that of membranes containing only DNP at a concentration of 50 µM (DNP, gray column; G m = 42.7 ± 5.9 nS/cm 2 ). Until now, only FAs have been shown to activate ANT1 directly (Figure 2A) [18,26,51,52].…”
Section: Dnp Increases the Proton Conductance Of The Membranes Reconstituted With Mitochondrial Membrane Proteinsmentioning
confidence: 99%
“…It was previously shown that ANT1 mediates proton transport in the presence of free long-chain fatty acids (FA), similar to UCPs [26,47,51]. To test whether DNP also activates ANT1, we used a well-defined model of planar bilayer membranes reconstituted with recombinant murine ANT1 (Figure S1) [27].…”
Section: Dnp Increases the Proton Conductance Of The Membranes Reconstituted With Mitochondrial Membrane Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…AAC is a member of the solute carrier family (SLC25) that exchanges ATP and ADP between the mitochondria matrix and the cytosol [45]. However, AAC has additional key functions: AAC is a fatty-acid induced proton channel that explains endogenous proton leak, as well as regulating the opening of the permeability transition pore and the removal of mitochondria by mitophagy [45,46]. Remarkably, both AAC-controlled leak and PTP opening can be stimulated by free fatty acids, similarly to how fatty acids activate UCP1 [45].…”
Section: Ucp1-independent Mechanisms Of Mitochondrial Uncouplingmentioning
confidence: 99%